Life Cycle Assessment (LCA) of Nutmeg Syrup Agroindustrial Products - Frangky Jessy Paat; Widiatmaka Widiatmaka; Moh. Yanuar Jarwadi Purwanto; Petrus Adam; Titi Candra Sunarti; Ronny Soputan (Sam Ratulangi University, 2022)
The engineering section is limited to the extraction of nutmeg flesh biomaterials. Another part of engineering is based on base flow inventory and product flow through the design of environmentally friendly plant energy input processes without fossil fuels. The purpose of this study was to compile a life cycle assessment (LCA) through reference to ISO 14040:2016 and ISO 14044:2017 for the development of agro-industrial products nutmeg syrup at PT. Hakatho Artha Industries in North Sulawesi. Substitution engineering without fossil fuels includes; nutmeg shell biochar substitution, POC biogas from nutmeg waste, nutmeg shell chitosan, and nutmeg organic waste eco enzyme. The biomaterial section of nutmeg flesh is limited by two methods of the extraction process. Determination of water content in nutmeg flesh samples based on the SNI 35544:2013 method with 91.72% (w/w) results. Determination of protein content refers to the method of SNI 01-2891-1992 with a result of 1.44% (w/w).Keywords: LCA, SNI, nutmeg syrup